Molecular phylogeny and identification of agromyzid leafminers in China, with a focus on the worldwide genus Liriomyza (Diptera: Agromyzidae) - Yong-xuan LIANG; Su-jie DU; Yu-jun ZHONG; Qi-jing WANG; Qiong ZHOU; Fang-hao WAN; Jian-yang GUO; Wan-xue LIU (Journal of Integrative Agriculture, 2023)
Leaf-mining flies (Diptera: Agromyzidae) are a diverse family of small-bodied insects that feed on living plant tissues as larvae. Various species in this family are considered globally invasive and have caused great agricultural economic losses. In China, economically important vegetable crops have been seriously damaged by these pest insects, especially by species of the genus Liriomyza. However, these species are difficult to differentiate because of their morphological similarities, and the Chinese fauna remains poorly known. To explore the relevant pest species in China and their phylogeny, agromyzid leafminers were collected from 2016 to 2019, and identified based on morphological characteristics and DNA barcodes. In total, 27 species from five genera of Agromyzidae were sampled and identified, including 16 species of Liriomyza. Both mitochondrial and nuclear genes were used to reconstruct their phylogenetic relationships and estimate the divergence time. Highly congruent and well-supported phylogenetic trees were obtained using the Bayesian inference and maximum-likelihood methods. This analysis revealed two main clades in Liriomyza, and clade 2 was inferred to have diverged from clade 1 approximately 27.40 million years ago (95% highest posterior density: 23.03–31.52 million years ago) in the Oligocene. Differences were observed in the distribution patterns and host associations between the Liriomyza clades. Clade 2 species are distributed in cool, high-latitude environments, suggesting that they may have evolved into a cool-adapted lineage.